Hunger watch report 2007-08 : the justice of eating - the struggle for food and dignity in recent humanitarian crises - Swan, Samuel Hauenstein; Vaitla, Bapu (Pluto, 2007)
The first annual report from leading NGO Action Against Hunger, this survey of the causes and consequences of acute malnutrition presents a comprehensive global overview of the problems of hunger and starvation.